Extremely Early Onset Transthyretin Familial Amyloid Polyneuropathy with a Leu55Pro Mutation: A Pediatric Case Report and Literature Review - Lee, Yun Jeong; Oh, Jeeyoung; Hwang, Su-Kyeung; Lee, Eun Joo; Yang, Dong Heon; Kim, Yong-Jin; Kwon, Soonhak; Hyun, Myung Chul (Neuropediatrics, 2019)
Transthyretin familial amyloid polyneuropathy (TTR-FAP) is a life-threatening autosomal dominant disease caused by the deposition of amyloid fibrils composed of TTR proteins. Symptoms of this disease include progressive sensorimotor neuropathy, cardiomyopathy, and involvement of other organs. We described a pediatric case of extremely early onset TTR-FAP with a TTR Leu55Pro mutation. A 17-year-old boy began to suffer from lower limb weakness, gait disturbance, and decreased sensation from 14 years of age onward. He presented with hypertrophic cardiomyopathy, periorbital and scleral ecchymosis, anhidrosis, orthostatic intolerance, and gastrointestinal autonomic dysfunction including nausea, vomiting, and diarrhea alternating with constipation. The patient's older sister had developed similar gastrointestinal symptoms from 20 years of age onward and was diagnosed as having hypertrophic cardiomyopathy. The boy's biopsy results showed infiltrated amyloid deposition on subcutaneous fat tissue and endocardium. Genetic analysis of the TTR gene demonstrated that both the patient and his sister had a pathogenic mutation, c.224T > C (Leu55Pro). Both patients were prescribed tafamidis, a TTR stabilizing agent. Although a majority of TTR-FAPs occur during adulthood, it should be suspected, even in pediatric populations, when symmetric length dependent neuropathy occurs in conjunction with a family history of neuropathy, autonomic neuropathy, and/or cardiomyopathy.
Keywords: amyloid neuropathy; transthyretin; Leu55Pro; early onset